The rule of the hand and its jurisprudential applications (Journal of the College of Basic Education, 2022)
The rule of hand is one of the rules that the faqih adopts in transactions and the judiciary to rule through ownership, so whoever has the right to seize something so that the thing was in his possession, and after his dependencies, that seizure is a sign of ownership. On his ownership of that thing, unless it arises between him and the like to the contrary, then the dictate of the hand falls into consideration, as he expressed the rule of the hand as a metaphor for appropriation and the thing being under the person’s disposal and in his possession, and it is not intended to be prejudicial, specific to the truth